Addressing the Early-Successional Habitat Needs of At-Risk Species on Privately Owned Lands in the Eastern United States - John A. Litvaitis (MDPI AG, 2021)
Public lands alone are insufficient to address the needs of most at-risk wildlife species in the U.S. As a result, a variety of voluntary incentive programs have emerged to recruit private landowners into conservation efforts that restore and manage the habitats needed by specific species. We review the role of one such effort, Working Lands for Wildlife (WLFW), initiated by the Natural Resources Conservation Service in partnership with the U.S. Fish and Wildlife Service. Using two at-risk species in the eastern U.S. (where private lands dominate), we show the substantial potential that WLFW has for restoring and maintaining needed habitats. Monitoring how effective these efforts are on populations of the target species has been challenging, and both monitoring and implementation are being modified in response to new information. Identifying landowner motivations is essential for developing long-term relationships and conservation success. As WLFW projects develop, they are moving toward a more holistic ecosystem approach, within which the conservation goals of at-risk species are embedded.